Modulation of the vibrational and optical properties in β copper phthalocyanine under compression - Du, Miaomiao; Wang, Shengyi; Fu, Shengchun; Zhang, Junkai (Journal of applied physics, 2024)
Because copper phthalocyanine (CuPc) has significant uses in industrial devices and pigments, it is a subject of great interest in basic scientific research. Studying and adjusting its photoelectric qualities, in particular, has drawn much attention. In this work, in situ high-pressure experiments were used to investigate in detail the vibrational and optical properties of ground-state β-CuPc up to 13 GPa. Both micro-Raman and ultraviolet and visible light (UV–vis) absorption measurements revealed a phase transition occurring around 3 GPa. Notably, the macrocycle breathing vibration was found to have a remarkable characteristic of first weakening and then strengthening in response to this pressure-induced phase transition. The UV–vis absorption data revealed that the bandgaps corresponding to the two absorption edges decrease gradually with increasing pressure, with one edge disappearing entirely above 11 GPa. Furthermore, the blue β-CuPc can be adjusted to dark green at 10 GPa and ultimately entirely black due to the merging of its absorption bands and redshifts at high pressure. This work improves our understanding of CuPc's intrinsic characteristics under harsh settings and manipulates its color effectively.